2013
DOI: 10.1007/s00256-013-1785-2
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of bone with secondary aneurysmal bone cyst-like change producing β-human chorionic gonadotropin

Abstract: Giant cell tumor of bone is a benign, locally aggressive neoplasm that is composed of sheets of neoplastic mononuclear cells interspersed amongst non-neoplastic, uniformly distributed, osteoclast-like giant cells. They represent approximately 4-5% of primary bone tumors. Rarely, bone tumors have been noted to produce human chorionic gonadotropin, a finding most often reported in osteosarcoma. We present the case of a young woman who presented with a low-level human chorionic gonadotropin level which, after res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…6 Although beta-hCG immunoreactivity and secretion have not been studied in a larger series of bone tumors, case reports have described markedly higher levels of serum beta-hCG elevation in osteosarcomas than in benign giant cell tumors, which raises the question of whether malignant bone neoplasms have a greater potential toward paraneoplastic hormone production than benign tumors and whether immunohistochemical expression could potentially be used as an marker of malignant phenotype. 9,10,21 The discrepancy between immunolabeling for beta-hCG and its clinical function (serum hormone elevation) seen in several of our patients can be explained in several ways. It has been proposed that neoplastic cells may secrete hormone at a rate that precludes hormone accumulation to a detectable level by immunohistochemical methods.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…6 Although beta-hCG immunoreactivity and secretion have not been studied in a larger series of bone tumors, case reports have described markedly higher levels of serum beta-hCG elevation in osteosarcomas than in benign giant cell tumors, which raises the question of whether malignant bone neoplasms have a greater potential toward paraneoplastic hormone production than benign tumors and whether immunohistochemical expression could potentially be used as an marker of malignant phenotype. 9,10,21 The discrepancy between immunolabeling for beta-hCG and its clinical function (serum hormone elevation) seen in several of our patients can be explained in several ways. It has been proposed that neoplastic cells may secrete hormone at a rate that precludes hormone accumulation to a detectable level by immunohistochemical methods.…”
Section: Discussionmentioning
confidence: 87%
“…6 Although beta-hCG immunoreactivity and secretion have not been studied in a larger series of bone tumors, case reports have described markedly higher levels of serum beta-hCG elevation in osteosarcomas than in benign giant cell tumors, which raises the question of whether malignant bone neoplasms have a greater potential toward paraneoplastic hormone production than benign tumors and whether immunohistochemical expression could potentially be used as an marker of malignant phenotype. 9,10,21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fitzhugh et al . found that the development of GCTB is usually accompanied by the production of β-HCG [ 14 ]. Lawless et al .…”
Section: Introductionmentioning
confidence: 99%